Infective endocarditis caused by Cardiobacterium valvarum - Washio, Yohei (Microbiology Society, 2019)

(untitled) (Access Microbiol)
We report a case with infective endocarditis (IE) due to Cardiobacterium valvarum . The patient was a 57-year-old male, who was referred to our hospital based on suspected IE detected by transthoracic echocardiography at a neighbourhood clinic. Three sets of blood cultures obtained on admission yielded positive results, and revealed rather slender and linear Gram-negative bacilli with a rosette formation that dyed minimally, with a pale white appearance. Although no isolates were identified by conventional methods, C. valvarum was ultimately identified by 16 S ribosomal RNA genotyping. HACEK group strains are difficult to identify by conventional methods. Therefore, if Gram-negative bacilli are isolated from IE patients, 16 S ribosomal RNA genotyping will be necessary. Furthermore, IE due to C. valvarum is very rare. We thus discuss our case in comparison with previous reports.